The Biodiversity of Food and Agriculture (Agrobiodiversity) in the Anthropocene: Research Advances and a Conceptual Framework - Zimmerer, Karl S.; Haan, Stef de; Jones, Andrew D.; Creed-Kanashiro, Hilary M.; Tello, Milka; Carrasco, Miluska; Meza, Krysty; Amaya, Franklin Plasencia; Cruz García, Gisella S.; Tubbeh, Ramzi; Jiménez Olivencia, Yolanda (Elsevier, 2019)
Multiple knowledge systems are crucial to understand human-environment interactions of the biodiversity of agriculture and food systems (agrobiodiversity). This article synthesizes these knowledge systems to formulate the novel Agrobiodiversity Knowledge Framework comprised of four themes: (1) ecology and evolution; (2) governance; (3) food, nutrition, and health; and (4) global environmental and socioeconomic changes. Resulting characterization of these knowledge themes, joined with cross-theme integration, demonstrate advances of agrobiodiversity research, management, and policy amid the accelerated global environmental and socioeconomic transformations of the Anthropocene. Framework results guide the presentation of new data from the Agrobiodiversity, Food, and Nutrition project (AFN) in Peru. These results integrate an emphasis on factors of global change, including climate change. The combination of the new knowledge framework and project results is utilized to point toward future directions for research, policy, and management. The Agrobiodiversity Knowledge Framework is essential to address the transformative planetary challenges of the Anthropocene that include sustainable development with nutritional security, biodiversity conservation, social justice, climate change, and nutrient pollution. Strengthening the focus on and analysis of the complex human-environment interactions of biodiversity in agriculture and food is vital as a nexus of science, scholarship, management, and policy in the era of Earth systems dominated by human activity.